2010
DOI: 10.1111/j.1471-4159.2010.06705.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the c‐Jun N‐terminal kinase pathway in retinal excitotoxicity, and neuroprotection by its inhibition

Abstract: J. Neurochem. (2010) 113, 1307–1318. Abstract Retinal excitotoxicity is associated with retinal ischemia, and with glaucomatous and traumatic optic neuropathy. The present study investigates the role of c‐Jun N‐terminal kinase (JNK) activation in NMDA‐mediated retinal excitotoxicity and determines whether neuroprotection can be obtained with the JNK pathway inhibitor, d‐form of JNK‐inhibitor 1 (d‐JNKI‐1). Young adult rats received intravitreal injections of 20 nmol NMDA, which caused extensive neuronal death i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 40 publications
3
30
2
Order By: Relevance
“…Several molecules, such as FADD/caspase8, MAPKs, and NF-jB have been proposed to be downstream of TNF-a in the apoptotic pathway (Andera, 2009). Studies have shown that NMDA induces phosphorylation of MAPKs (p-JNK and p-p38) and that the inhibition of its phosphorylation protects neural cells in the RGCL and the INL Bessero et al, 2010). According to these reports and the present study, there is a good possibility that thalidomide inhibits the phosphorylation of MAPKs with suppression of TNF-a as an upstream of these proteins.…”
Section: Discussionsupporting
confidence: 72%
“…Several molecules, such as FADD/caspase8, MAPKs, and NF-jB have been proposed to be downstream of TNF-a in the apoptotic pathway (Andera, 2009). Studies have shown that NMDA induces phosphorylation of MAPKs (p-JNK and p-p38) and that the inhibition of its phosphorylation protects neural cells in the RGCL and the INL Bessero et al, 2010). According to these reports and the present study, there is a good possibility that thalidomide inhibits the phosphorylation of MAPKs with suppression of TNF-a as an upstream of these proteins.…”
Section: Discussionsupporting
confidence: 72%
“…S2A). Supporting the biological relevance of this finding, MKK7 and its homolog, MKK4, are the canonical activators of JNK1-3 (27), key regulators of RGC cell death (9)(10)(11)(12). As an additional validation that our siRNA finding was specifically a result of DLK pathway inhibition, RGCs were isolated from mice containing a floxed allele of Dlk (22) or wildtype controls and then transduced with adenovirus expressing the P1 bacteriophage Cre recombinase or a GFP control.…”
Section: Resultsmentioning
confidence: 54%
“…Moreover, it establishes the proof of principle for a whole-genome scan in primary RGCs to identify additional potential neuroprotective pathways and drug targets. Several previous studies have implicated the JNK pathway in both traumatic and glaucomatous models of optic neuropathy (9)(10)(11)(12). However, the mechanism by which axonal injury leads to JNK activation in RGC cell bodies has been unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to protein tyrosine kinases that promote neuronal survival, there are several pro-apoptotic protein kinases that contribute to RGC death, such as the c-Jun N-terminal kinase. 84 c-Jun, activated by c-Jun N-terminal kinase phosphorylation, mediates transcription of pro-apoptotic genes and has been shown to be upregulated in rat and monkey models of glaucoma. 85,86 siRNA-mediated gene expression knockdown of c-Jun in RGCs resulted in a threefold increase in RGC survival at 2 weeks after optic nerve lesion.…”
Section: Inhibition Of Apoptotic Pathways and Manipulation Of Mitochomentioning
confidence: 99%